Request Strategies used by the Main Character in the Movie â€œThe Blind Sideâ€ (Universitas Islam Negeri Sunan Ampel Surabaya, 2015)
This study focuses on the request strategies used by the female main character (Leigh Anne Tuohy) in the movie ‘The Blind Side’. In conducting her analysis, the writer is very much indebted to Trosborg, 1995, especially, through his theory of request strategies. The writer used qualitative approach by applying interpretive framework in describing the data. Leigh Anne Tuohy‘s utterances which contain request strategies are the data source of this study. The results show that there are ten types of request strategies used by the female character in the movie. In addition to finding the types of request strategies, the writer also describes the situation and condition of the main character when she is giving the requests to some body else.